Understanding social media: how to create a plan for your business that works - Damian Ryan (London: Kogan Page Limited, 2015)
"Understanding Social Media is a companion title to the highly successful Understanding Digital Marketing. Accessible and practical, this book draws on the experiences of over 200 marketers to create a comprehensive guide to current practice including:- Creating a social media program - Understanding stakeholders such as blogs, networks and Web 2.0 - Rules governing the relationship between search and social - Case studies from successful and failed campaigns - Budgeting for social media activities - How to set key performance indicators (KPIs) - Understanding social media ROI - Customer experience - Building a social media team - Analytics and creating a social media dashboard - Risk assessment and risk management in social media "--
"Understanding Social Media is the essential guide to social media for students and professionals alike. Drawing on the experience, advice and tips of over 200 digital marketers and interviews with social media superstars, it is an extensive crowd-sourced guide to social media platforms. Illustrated throughout with case studies from both successful and failed campaigns, Understanding Social Media democratizes knowledge of social media and promotes best practice, answering questions such as 'How do you create a compelling social media campaign?', 'How do you build and engage with an audience?' and 'Where is the line between online PR and social media drawn?' It is the most comprehensive and practical reference guide to social media available"--
Keywords: Internet Marketing; Social Media; Marketing; Strategic Planning; Management; Applied Sciences